The Minimal Difference as an Individual Threshold to Examine the Utility of a Verification Bout in Determining V̇O 2max - Succi, Pasquale J; Benitez, Brian; Kwak, Minyoung; Bergstrom, Haley C (Medicine and science in sports and exercise, 2023)
A square-wave verification bout to confirm maximal oxygen uptake (V̇O 2max ) from a graded exercise test (GXT) has been recommended based on mean responses. This study used the test-retest reliability, mean, and individual differences between the highest V̇O 2 from the GXT (V̇O 2GXT ) and verification bout (V̇O 2verification ) to examine the efficacy of a verification bout in the determination of O 2max in healthy, recreationally trained, well-motivated men. Ten men (24 ± 4 yr) completed a GXT on a cycle ergometer followed by a submaximal verification bout to determine V̇O 2GXT and V̇O 2verification . After completion of the initial GXT, subjects rested for 5 min then performed the verification bout at 90% of the peak power output from the initial GXT. Analyses included a two-way repeated-measures ANOVA, intraclass correlation coefficients (ICC 2,1 ), standard errors of the measurement (SEM), minimal differences (MD), and coefficients of variation (COV). There was no test (test 1 vs test 2)-method (GXT vs verification) interaction ( P = 0.300) and no main effect for test ( P = 0.690), but there was a main effect for method ( P = 0.003). The V̇O 2GXT (46.0 mL⋅kg -1 ⋅min -1 ) was significantly greater than V̇O 2verification (43.9 mL⋅kg -1 ⋅min -1 ), collapsed across test. The V̇O 2GXT (ICC = 0.970, SEM = 1.63 mL⋅kg -1 ⋅min -1 , MD = 4.51 mL⋅kg -1 ⋅min -1 , COV = 3.54%) and the V̇O 2verification (ICC = 0.953, SEM = 1.87 mL⋅kg -1 ⋅min -1 , MD = 5.17 mL⋅kg -1 ⋅min -1 , COV = 4.25%) demonstrated "excellent" reliability. No subject exceeded the MD test-retest for V̇O 2GXT or V̇O 2verification . No subject had a V̇O 2verification that exceeded V̇O 2GXT by more than the MD, but two subjects had a V̇O 2GXT , which exceeded V̇O 2verification by more than the MD. The excellent reliability of V̇O 2GXT in addition to the examination of the individual differences between V̇O 2GXT and V̇O 2verification using the MD indicated that a standalone GXT was sufficient to determine V̇O 2max .